2021
DOI: 10.1094/pdis-10-20-2114-re
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Colletotrichum Species Associated with Anthracnose Disease of Strawberry in Sichuan Province, China

Abstract: Strawberry anthracnose, caused by Colletotrichum species, is a major fungal disease threatening strawberry industry in Sichuan Province of southwestern China. However, research on identification of Colletotrichum species associated with strawberry anthracnose in Sichuan remains uncovered. In this study, 73 representative Colletotrichum strains were isolated from diseased leaves, stolons, petioles and crowns of 11 major strawberry planting localities in Sichuan Province. Based on morphological characteristics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The morphological characteristics of Colletotrichum species are associated with factors of the cultivation environment, such as wetness, temperature, light, and growth media. In addition, species within the Colletotrichum complex have not been distinguished from one another because of their similar morphological characteristics [6,9]. Therefore, we jointly used multilocus phylogenetic and morphological characteristic analyses to identify the pathogen of anthracnose [10,39,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphological characteristics of Colletotrichum species are associated with factors of the cultivation environment, such as wetness, temperature, light, and growth media. In addition, species within the Colletotrichum complex have not been distinguished from one another because of their similar morphological characteristics [6,9]. Therefore, we jointly used multilocus phylogenetic and morphological characteristic analyses to identify the pathogen of anthracnose [10,39,42].…”
Section: Discussionmentioning
confidence: 99%
“…Anthracnose is a destructive disease in the strawberry field that can affect the health of the plant at any stage, particularly during the seedling and transplanting stage [4]. For example, the incidence of anthracnose at the seedling stage reaches 50 to 80% under disease-favorable conditions of wetness and temperature, resulting in severe seedling death and yield loss [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…), Citrus spp., mango (Mangifera indica), peach (Prunus persica), pear (Pyrus spp. ), strawberry (Fragaria × ananassa) and tea (Camellia sinensis), possibly due to its parasitic and endophytic lifestyle [18,40,[44][45][46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…It can infect many plants and cause many diseases (Weir et al, 2012), such as crown rot in strawberries (Luo et al, 2021), as well as anthracnose disease and leaf disease in many plants, including Citrus spp., Piper nigrum, Artocarpus heterophyllus, Artocarpus sericicarpus, Coffea arabica, Coffea canephora, Eriobotrya japonica, Ficus carica, Mentha sp., Rosmarinus officinalis, Theobroma cacao, Jasminum sambac, Pongamia pinnata, Bauhinia forficata subsp. pruinose and Macadamia integrifolia, (Wikee et al, 2011;James et al, 2014;Larran et al, 2015;Dwarka et al, 2016;Qiu et al, 2020;Jian et al, 2021;Perez-Mora et al, 2021;Wang et al, 2021). Casas et al (2021a, b) reported that C. siamense can be endophytic and is used as a biological control in anthracnose disease.…”
Section: Discussionmentioning
confidence: 99%